mlo5, a resistance gene effective against a biotrophic pathogen (Blumeria graminis fsp. hordei) confers enhanced susceptibility of barley to the necrotrophic fungus Bipoláris sorokiniana (teleomorph: Cochliobolus sativus) - Király, Lóránt (Acta Biologica Szegediensis, 2002)
The barley resistance gene m/o5 determines race non-specific resistance to the biotrophic powdery mildew pathogen Blumeria graminis f.sp. hordei. On the other hand, we have shown that barley lines that contain the mlo5 gene display enhanced susceptibility to the necrotrophic fungus Bipoláris sorokiniana (teleomorph: Cochliobolus sativus) and its toxic culture filtrate (Kumar et al. 2001). Enhanced susceptibility to necrotic disease symptoms was linked to increased accumulation of hydrogen peroxide (H}02), a reactive oxygen intermediate. In addition, increased accumulation of transcripts of a barley pathogenesis-related gene (PR1-b) and slight increases in expression of two antioxidant genes, a glutathione S transferase and an ascorbate peroxidase occurred in association with enhanced cell/tissue death and Hj02 accumulation. These results might reflect an unsuccessful attempt by infected m/o5-barley to suppress necrotic disease symptoms and support the hypothesis that the barley Mlo gene product functions as a negative regulator of cell death. Therefore, a compromised Mlo pathway confers effective control of the biotrophic powdery mildew pathogen but not of the necrotroph B. sorokiniana, demonstrating the necessity of different host defense strategies in response to pathogens with different lifestyles (biotroph vs. necrotroph).